2017
DOI: 10.1080/08952841.2017.1313017
|View full text |Cite
|
Sign up to set email alerts
|

Woman to Woman (W2W): Adapting an HIV risk reduction intervention for older women

Abstract: Woman to Woman (W2W) is a novel adaptation of the Sisters Informing Sisters about Topics on AIDS (SISTA) HIV prevention program. This article describes the process of adapting and piloting W2W based on recommendations from existing HIV prevention research. Six older women, all of whom had histories of homelessness and the majority of whom identified as African American, enrolled in the study, which piloted the adapted intervention and materials, evaluated the acceptability of the program, and assessed the meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Older African American women, in fact, desire such information. For example, Conner et al (2018) found in an evaluation of the feasibility of a pilot HIV intervention that older women were satisfied with an explicit focus of the intervention on HIV knowledge. In the focus groups we convened, many women asked for an additional session in which they could learn more about HIV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Older African American women, in fact, desire such information. For example, Conner et al (2018) found in an evaluation of the feasibility of a pilot HIV intervention that older women were satisfied with an explicit focus of the intervention on HIV knowledge. In the focus groups we convened, many women asked for an additional session in which they could learn more about HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Culturally tailored HIV messages and programs are needed to address sociocultural factors unique to this population (Conner et al, 2018). For example, messages might discuss the stigma of sexuality and ageism and how this relates to HIV protective behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Targeting this group with tailored, aging-specific educational materials can increase awareness and reduce stigma associated with HIV. 3…”
Section: Introductionmentioning
confidence: 99%